2017
DOI: 10.1007/s40520-017-0742-7
|View full text |Cite
|
Sign up to set email alerts
|

A prevalence study of potentially inappropriate medications use in hospitalized Pakistani elderly

Abstract: Our findings support the need for measures to improve the quality of drug treatment in the elderly Pakistani population, especially among dependent patients with polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Due to this reason, a national survey in the USA described the use of insulin among 206 older patients per 100,000 outpatient prescription visits as one of the major reasons for unplanned hospitalization [ 45 ]. Another study conducted in Karachi, Pakistan had revealed that at least 1 PIM was prescribed to more than half (64%) of the older population [ 46 ]. It is suggested that many of the PIMs like antihistaminic agents (e.g., diphenhydramine), proton pump inhibitors (e.g., omeprazole and esomeprazole) and analgesics (e.g., aspirin and non-steroidal anti-inflammatory drugs (NSAIDS)) are more frequently used by older people than any other age group [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this reason, a national survey in the USA described the use of insulin among 206 older patients per 100,000 outpatient prescription visits as one of the major reasons for unplanned hospitalization [ 45 ]. Another study conducted in Karachi, Pakistan had revealed that at least 1 PIM was prescribed to more than half (64%) of the older population [ 46 ]. It is suggested that many of the PIMs like antihistaminic agents (e.g., diphenhydramine), proton pump inhibitors (e.g., omeprazole and esomeprazole) and analgesics (e.g., aspirin and non-steroidal anti-inflammatory drugs (NSAIDS)) are more frequently used by older people than any other age group [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A national survey in the USA described that the use of insulin among 206 elderly patients per 100,000 outpatient prescription visits is one of the major reasons for unplanned hospitalization because of its association with hypoglycemic events and seizures 36. Another study conducted in Karachi, Pakistan, had declared that at least one PIM was prescribed to 64% of the geriatric population 37. It is estimated that antihistaminic agents (eg, diphenhydramine), proton pump inhibitors (eg, omepra-zole and esomeprazole), and analgesics (eg, aspirin and nonsteroidal anti-inflammatory drugs) are more frequently used by elderly people than by any other age groups 3840.…”
Section: Discussionmentioning
confidence: 99%
“…[52] As osteoarthritis and other musculoskeletal problems are very common in the elderly, they are often prescribed NSAIDs and take them on a regular basis. [53] The findings of our study indicate that nearly two-thirds (61.8%) of prescriptions had DDIs. This is in line with a study conducted in Northern Ethiopia which reported a prevalence of 62.2% for drug interactions among elderly patients.…”
Section: Discussionmentioning
confidence: 54%
“…The NSAIDs are categorized as the commonest prescribed analgesics, especially in ambulatory settings . As osteoarthritis and other musculoskeletal problems are very common in the elderly, they are often prescribed NSAIDs and take them on a regular basis …”
Section: Discussionmentioning
confidence: 99%